Construction, Rescue, and Characterization of Vectors Derived from Ovine Atadenovirus - Löser, Peter (American Society for Microbiology, 2003)
Gene transfer vectors derived from ovine atadenovirus type 7 (OAdV) can efficiently infect a variety of mammalian cells in vitro and in vivo to deliver and express transgenes. However, early OAdV vectors were designed on human mastadenovirus principles prior to the complete characterization of OAdV genes and transcripts. The distinctive arrangement of the OAdV genome has suggested ways to improve OAdV vector design and utility. We therefore developed a cosmid-based approach that allows efficient construction of recombinant ovine atadenovirus genomes in which the transgene is inserted at one of three sites. Viruses were rescued by transfection of viral DNA into a new ovine fetal skin fibroblast producer cell line, HVO156. The suitability of the three insertion sites was compared with respect to virus rescue efficiency, gene expression levels, and genetic stability of the vectors. We found that one vector with a transgene inserted at site 1, between the pVIII and fiber genes, was unstable. Only one vector that carried a transgene at site 2, near the right end of the genome, together with a nearby deletion was rescued. In contrast, several vectors with different transgenes inserted in site 3, between the E4 and RH transcription units, were repeatedly rescued, and these vectors were stable over at least four passages. Transgene orientation in site 3 had only little effect on expression. Finally, a vector carrying a human factor IX cDNA at site 3, when administered intravenously, produced nearly physiological levels of human factor IX in mice. The availability of an efficient method for vector construction and the identification of a new insertion site for virus rescue and gene expression substantially enhance the utility of the OAdV vector system.